Book Reviews (Journal of Finance, 1993)
Book reviewed in this article: The Reform of Federal Deposit Insurance: Disciplining the Government and Protecting Taxpayers . Edited by JAMES R. BARTH and R. DAN BRUMBAUGH, JR. New York: Harper Business, 1992. Pp. xxi + 310. Nonlinear Dynamics, Chaos, and Instability . By WILLIAM A. BROCK, DAVID A. HSIEH, and BLAKE LEBARON. Cambridge, MA: MIT Press, 1992. Pp. xviii + 328. Options and Financial Futures: Valuation and Uses . By DAVID A. DUBOF‐SKY. New York: McGraw‐Hill, 1992. Pp. xx + 699. The Economic Structure of Corporate Law . By FRANK H. EASTERBROOK and DANIEL R. FISCHEL. Cambridge, MA: Harvard University Press, 1991. Pp. viii + 370. Managing Corporate Pension Plans . By DENNIS E. LOGUE, New York: Harper Collins Inc., 1991. Pp. x + 289. Sense & Nonsense in Corporate Finance . By LOUIS LOWENSTEIN. Reading, MA: Addison‐Wesley Publishing Company, Inc., 1991. Pp. viii + 263. Economics, Organization and Management . By PAUL MILGROM and JOHN ROBERTS. Englewood Cliffs, NJ: Prentice‐Hall, 1992. Pp. xvii + 621.